Mapping the castor bean endosperm proteome revealed a metabolic interaction between plastid, mitochondria, and peroxisomes to optimize seedling growth - Wrobel, Thomas J.; Brilhaus, Dominik; Stefanski, Anja; Stühler, Kai; Weber, Andreas P. M.; Linka, Nicole (Frontiers in Plant Science, 2023)
In this work, we studied castor-oil plant Ricinus communis as a classical system for endosperm reserve breakdown. The seeds of castor beans consist of a centrally located embryo with the two thin cotyledons surrounded by the endosperm. The endosperm functions as major storage tissue and is packed with nutritional reserves, such as oil, proteins, and starch. Upon germination, mobilization of the storage reserves requires inter-organellar interplay of plastids, mitochondria, and peroxisomes to optimize growth for the developing seedling. To understand their metabolic interactions, we performed a large-scale organellar proteomic study on castor bean endosperm. Organelles from endosperm of etiolated seedlings were isolated and subjected to liquid chromatography-tandem mass spectrometry (LC-MS/MS). Computer-assisted deconvolution algorithms were applied to reliably assign the identified proteins to their correct subcellular localization and to determine the abundance of the different organelles in the heterogeneous protein samples. The data obtained were used to build a comprehensive metabolic model for plastids, mitochondria, and peroxisomes during storage reserve mobilization in castor bean endosperm.